Local e-government information and service delivery - Dias, G.P. (2011)
In this article we present a survey of the websites of 239 Portuguese municipalities. General characteristics of the web sites, available information and online delivery of services were observed. The study was conducted between February and May, 2010. Considering the results, we conclude that, despite the investments made in the past decade, local e-government in Portugal still exhibits medium level development in what relates information dissemination and remains substantially underdeveloped concerning online service delivery. We argue that a cultural breakthrough is needed in order to take full advantage of new technologies in government-to-citizen interactions at the local level in Portugal. © 2011 AISTI.